Protective Efficacy of an Inactivated Recombinant Serotype 4 Fowl Adenovirus Against Duck Adenovirus 3 in Muscovy Duck - Yun Lin; Wenjie Jiang; Lihua Ma; Jiayu Zhang; Ye Tang; Qiuqi Kan; Haifeng Xiong; Jiayan Wu; Jun Zhang; Yiwen Niu; Wei Zhang; Shengnan Wang; et al. (Vaccines)
Background: Duck adenovirus 3 (DAdV-3) is an emerging pathogen that has caused severe economic losses to the duck industry in China. Recently, the infection of ducks with serotype 4 fowl adenovirus (FAdV-4) has also been reported in China. Therefore, an efficient bivalent vaccine to control the diseases caused by DAdV-3 and FAdV-4 is extremely urgent. In our previous study, a recombinant FAdV-4 expressing Fiber-2 of DAdV-3 was generated and designated as rFAdV-4-Fiber-2/DAdV-3. Methods: Here, the recombinant virus rFAdV-4-Fiber-2/DAdV-3 was inactivated to serve as a bivalent vaccine, and its immunogenicity and protective efficacy against DAdV-3 were evaluated in Muscovy ducks. Results: The subcutaneous injection of rFAdV-4-Fiber-2/DAdV-3 could efficiently induce antibodies against Fiber-2 of DAdV-3 and neutralize antibodies against FAdV-4. After challenges with DAdV-3, in comparison with the non-immunized ducks, the immunized ducks did not show any bodyweight loss, gross lesions, or histopathologic change. Moreover, viral loads in livers and kidneys from immunized ducks were undetectable, whereas those in non-immunized ducks with challenge were significantly high. Conclusions: All these data demonstrate that the inactivated recombinant virus rFAdV-4-Fiber-2/DAdV-3 has the potential to be an efficient vaccine candidate against both FAdV-4 and DAdV-3, although efficacy for FAdV-4 needs to be confirmed experimentally.